Evaluation of 25-hydroxy vitamin d3 levels in patients with small uterine myomas - Abdel-Kader, Mariam h.; Olama, Magdy A.; Hamdy, Enas M. (International journal of health sciences, 2022)
Background; Uterine fibroid are the most frequent benign pelvic tumors between women in reproductive period group that has multifactorial pathogenesis. Modern ideas of uterine fibroid pathogenesis have included vitamin D as a vital component. Aim and objectives; was to study the link between 25-hydroxy vitamin D3 levels in cases having small uterine myomas. Subjects and methods; This is a case-control study, was conducted at the Gynecology and Obstetrics department outpatient clinic at Al Zahraa University Hospitals, on 60 women divided into two groups: (Study group); included Thirty cases having fibroid uterus, (Control group); included Thirty women who had no fibroid uterus. Result; When compared to controls, vitamin D3 levels in cases were considerably lower. Conclusion; Vitamin D looks to be a promising and valuable anti-UF treatment. More large, well-designed randomized clinical trials are needed to look into the effectiveness of vitamin D in females with UFs of all ethnicities, especially those of color who are at higher risk of vitamin D deficiency. As a result, vitamin D may become a viable treatment choice for UF, with the added benefit of its pleiotropic impact.